Artificial intelligence with the application in medicine and dentistry - Roongruangsilp, P.; Khongkhunthian, P. (Journal of Osseointegration, 2022)
Aim To review and summarize the current literature on the concept, history as well as the current and tentative applications of artificial intelligence in medicine and dentistry. Methods Data sources: Collection of data were taken from Electronic databases such as PubMed, Scopus, arXiv and google scholar. Study selection: Full-text articles and conference-proceedings regarding artificial intelligence, artificial neural network, machine learning, deep learning, and big data, and related articles in the medical and dental field were included in this review. Conclusions Artificial intelligence is a breakthrough technology that is rapidly progressing and has been continuously implemented to achieve maximum human utility. With the enormous increase in documented information and the large amounts of recorded patient data along with the emergence of this technology, the use of machine learning and deep learning have recently become a necessity in modern healthcare. These technologies can also serve as a useful modality for several applications within these fields. Notwithstanding these many advancements, artificial intelligence still has some limitations, but its opportunity is limitless, as there is still tremendous potential for consecutive research in the medical and dental fields.